2014
DOI: 10.1108/tr-06-2013-0037
|View full text |Cite
|
Sign up to set email alerts
|

Leadership networks in destinations

Abstract: Purpose – Co-operation activities play a central role for the development of a tourism destination, and require a co-operative approach among numerous different actors to manage and market a tourism destination. This paper aims to describe the characteristics of leadership networks in tourism destinations and their impact on destination development. Design/methodology/approach – The paper discusses network relationships of destination le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 45 publications
0
26
0
2
Order By: Relevance
“…In tourism, the stakeholder theory can be applied to a destination, and many authors have identified different stakeholders contributing to the tourism product, among them many independent businesses [8,22]: "The DMO shall act as a facilitator to achieve the strategic objectives of the destination" [30]. As independent units, these businesses are operated by individual entrepreneurs, none of whom have dominant administrative power at the destination [6,31].…”
Section: Stakeholder Theory and Its Application To Sustainable Tourismentioning
confidence: 99%
See 1 more Smart Citation
“…In tourism, the stakeholder theory can be applied to a destination, and many authors have identified different stakeholders contributing to the tourism product, among them many independent businesses [8,22]: "The DMO shall act as a facilitator to achieve the strategic objectives of the destination" [30]. As independent units, these businesses are operated by individual entrepreneurs, none of whom have dominant administrative power at the destination [6,31].…”
Section: Stakeholder Theory and Its Application To Sustainable Tourismentioning
confidence: 99%
“…Rural family firms typically depend on their surrounding natural environment and aim to conserve and develop their region's natural heritage [7]. Within community destinations, businesses are independent units operated by entrepreneurs, and no unit wields dominant administrative power within the destination [6,8]. Tirol's tourism destinations are divided into 34 districts, each with a destination management organization (DMO) [9].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of a tourism destination as a whole depends on the web of connections between the various players, and not only on the intrinsic characteristics of the destination (March and Wilkinson 2009). Contributions to destination governance often advocate a form of self-governance that depends on the cooperation between all relevant stakeholders, and aims to develop joint strategies and collective action (D'Angella and Go 2009, Jamal and Getz 1995, Palmer and Bejou 1995, Zehrer et al 2014. In principle, however, one cannot assume that a-priori a destinations' actors are willing to work together.…”
Section: (Tourism) Destination Business Ecosystemmentioning
confidence: 99%
“…A aglomeração de atividades econômicas e produtivas potencializam atividades de cooperação e desempenham um papel central para o desenvolvimento de um destino turístico. Entretanto, uma abordagem cooperativa entre numerosos atores do turismo demandam de liderança na rede para o desenvolvimento do destino (ZEHRER;. A atividade turística, tanto global como localmente, necessita de formas colaborativas e associativas que devem ser governadas a partir de redes de diferentes organizações e setores de negócios, tanto intra como interorganizacionais (ERKUS-ÖZTÜRK; ERAYDIN, 2010).…”
Section: Introductionunclassified